2017
DOI: 10.1007/s00792-017-0940-4
|View full text |Cite
|
Sign up to set email alerts
|

Membrane lipids and soluble sugars dynamics of the alkaliphilic fungus Sodiomyces tronii in response to ambient pH

Abstract: Alkaliphily, the ability of an organism to thrive optimally at high ambient pH, has been well-documented in several lineages: archaea, bacteria and fungi. The molecular mechanics of such adaptation has been extensively addressed in alkaliphilic bacteria and alkalitolerant fungi. In this study, we consider an additional property that may have enabled fungi to prosper at alkaline pH: altered contents of membrane lipids and cytoprotectant molecules. In the alkaliphilic Sodiomyces tronii, we showed that at its opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…The alkaline pH adaptation of Y. lipolytica caused a general decrease in the storage lipid profile (Figure 3). The similar decrease in the total storage lipids at alkaline ambient pH was also demonstrated for the Sodiomyces tronii ascomycete [20]. The decrease in DAG levels in storage lipids under thermal and combined stresses suggested that under these conditions, the cells could use the storage lipids as substrates ( Figure 3A).…”
Section: Lipidome Of Y Lipolyticasupporting
confidence: 70%
See 2 more Smart Citations
“…The alkaline pH adaptation of Y. lipolytica caused a general decrease in the storage lipid profile (Figure 3). The similar decrease in the total storage lipids at alkaline ambient pH was also demonstrated for the Sodiomyces tronii ascomycete [20]. The decrease in DAG levels in storage lipids under thermal and combined stresses suggested that under these conditions, the cells could use the storage lipids as substrates ( Figure 3A).…”
Section: Lipidome Of Y Lipolyticasupporting
confidence: 70%
“…Moreover, mannitol comprises more than half of the total sugar amount in the cytosol of some alkali-tolerant fungi, namely Acrostalagmus luteoalbus, Chordomyces antarcticus, and alkaliphile species of Sodiomyces magadii and S. alkalinus. Its relative composition increased while pH lowed to acidic pH [20]. The mannitol level in Y. lipolytica also increased at elevated concentrations of sodium chloride [12].…”
Section: Cytosol Carbohydrate Profilementioning
confidence: 97%
See 1 more Smart Citation
“…P-type vs. S-type; see Asiegbu, 2000). Moreover, Bondarenko et al (2017) L. Marynowski et al International Journal of Coal Geology 201 (2019) 51-61 found that some alkaliphilic fungi change their carbohydrate composition at a very high pH (glucose is substituted by mannitol and arabitol). The high concentration of fungal biomarkers in this Late Cretaceous section suggests their important role in this period of time.…”
Section: Implications For Differences In Saccharide Distribution and mentioning
confidence: 99%
“…Therefore, a collection of isolates from the White Sea marshy habitats [191] and soda solonchaks [192] was a focus of the project, generating a plethora of physiological and biochemical studies. Important stress tolerance mechanisms associated with the structure of membranes were deciphered using these collections [193].…”
Section: Microorganisms and Fungimentioning
confidence: 99%